How Joan Became Ivan [About Changes in the Bulgarian Anthroponymy from the Bulgarian National Revival Period] - Walczak-Mikołajczakowa, Mariola (Poznańskie Studia Slawistyczne, 2015)
The article depicts reflection over the issue of changes in the Bulgarian anthroponymy from the Bulgarian National Revival period, which usually consists in an inconsistent, i.e. concerning only several historical figures, substitution of the Greek form Joan by the native form- Ivan. Furthermore, the author does not comprehensively answer the questions how and why it happened, although they present the issue as a complex one and possible to conceptualize in myriad ways.